Strategic Planning for the Parenting Program at the Pembina Lintau Buo Kindergarten - Fania, Fira; Siska, Mery; Nuryasni, Nuryasni; Asmendri, Asmendri; Sari, Mila (Lembaga Penelitian dan Pendidikan Mandala, 2024)
Parenting programs in Kindergarten (TK) have a very important role in supporting children's development, both socially, emotionally and academically. This research aims to design an effective parenting program strategy at the Pembina Lintau Buo State Kindergarten. Through a qualitative approach, this research involves in-depth interviews, observation and documentation. The subjects in this research involved school principals, teachers and parents to gain a comprehensive perspective regarding parents' needs and expectations for their children's education. The research results show that planning and implementing a good parenting program can have a positive impact on parents and children, namely improving the quality of students' understanding in learning by involving parents' participation through parenting learning programs. The parenting programs implemented are: Parent gatherings, elementary classes, seminars on early childhood education, training/workshops, and home visits. Strategic planning in managing early childhood education can be carried out through steps such as identifying needs and problems, environmental studies, determining vision and mission, and preparing programs.